Evidence According to Provisions of Code of Civil Procedure of Serbia from 1865 - Kulauzov, Maša; Milutin, Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
The article sheds light on provisions of legislation on civil procedure of Serbia from 1865 concerning evidence in civil lawsuits, such as: testimony of witnesses, documentary evidence, experts testimony that is often necessary so that the trial judge can properly understand scientific or technical issues relevant to the lawsuit, and different kinds of oaths. Evidence is fundamental to the outcome of any civil litigation because, ordinarily, the facts in a civil lawsuit must be proved by evidence, and the judge will decide the civil case on the evidence adduced by the parties. As being fully aware of its significance, the author of the Code, minister of justice Rajko Lešjanin dedicated 125 paragraphs to evidence in civil lawsuits. They had been very carefully drafted after thorough and detailed discussion between the author of the draft and the State Councilʹs Commission. In 1872, minister of justice Stojan Veljković drafted amendments and supplements to a certain number of articles regarding proofs in litigation but, since Veljkovićʹs document was never enacted, these articles were left unrevised. However, a few paragraphs concerning evidence in civil cases were altered in 1885 and 1901. All aforementioned amendments and supplements, as well as provisions that remained intact during the whole period that the Code was in force, were meticulously scrutinized in this paper.